The local authority in the light of the challenges of energy transition - Korczak, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article addresses the role of local authority units in the energy transition process, which is crucial because energy generating systems are located in a specific municipality and they contain sources of emissions exerting a negative impact on the climate. Therefore, while the State’s central authorities form the legal framework for the activities of the municipalities, counties and voivodships, it is the actual activities of the voivodship assemblies and boards, the county councils and boards and the municipal councils and executive bodies that enable the planned parameters of this negative impact to be achieved. The article takes into account the obligations arising from Union law.
Keywords: local authority; energy transition; renewable energy sources; climate neutrality